2020
DOI: 10.1111/aogs.13800
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of maternal adipose tissue during 1st trimester screening for aneuploidies and risk of developing gestational diabetes

Abstract: Introduction:The objective of the present study is to compare the sonographic measurement of subcutaneous adipose thickness and visceral adipose thickness during 1st trimester screening for aneuploidies between non-diabetic pregnant women and patients who develop 1st trimester or 2nd trimester gestational diabetes mellitus (GDM). Material and methods:Adipose thickness was measured by transabdominal ultrasound imaging in pregnant women attending our clinic for screening for fetal aneuploidies between 11 and 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…Esses efeitos são decorrentes da ação térmica e mecânica as quais induzem tanto a necrose seletiva, quanto o processo de lipólise dos adipócitos, e secundariamente do aumento do metabolismo local visando a reparação tecidual, todos esses processos são mediados pela ação adrenérgica, podendo atingir um aumento da ação do sistema nervoso autônomo simpático. (D'Ambrosi et al, 2020) Na busca do equilíbrio da oferta e demanda de glicose no organismo, a insulina atua tanto na captação periférica de glicose quanto nos tecidos musculares e adiposos, nestes, a insulina estimula a lipogênese no fígado e reduz a lipólise nos adipócitos. (Czech, 2020) por meio do tratamento do ultrassom focado de alta potência atingiu a apoptose e necrose dos adipócitos, fato que implicou no aumento da oferta de triglicerídeos, ácidos graxos e a glicose para a corrente sanguínea, assim acredita-se ter favorecido a predominância parassimpática e o aumento dos índices rMSSD, HF ms 2 e SD1, no período de recuperação da terapêutica e contribuindo também para o incremento dos valores da modulação global e nos valores de colesterol.…”
Section: Discussionunclassified
“…Esses efeitos são decorrentes da ação térmica e mecânica as quais induzem tanto a necrose seletiva, quanto o processo de lipólise dos adipócitos, e secundariamente do aumento do metabolismo local visando a reparação tecidual, todos esses processos são mediados pela ação adrenérgica, podendo atingir um aumento da ação do sistema nervoso autônomo simpático. (D'Ambrosi et al, 2020) Na busca do equilíbrio da oferta e demanda de glicose no organismo, a insulina atua tanto na captação periférica de glicose quanto nos tecidos musculares e adiposos, nestes, a insulina estimula a lipogênese no fígado e reduz a lipólise nos adipócitos. (Czech, 2020) por meio do tratamento do ultrassom focado de alta potência atingiu a apoptose e necrose dos adipócitos, fato que implicou no aumento da oferta de triglicerídeos, ácidos graxos e a glicose para a corrente sanguínea, assim acredita-se ter favorecido a predominância parassimpática e o aumento dos índices rMSSD, HF ms 2 e SD1, no período de recuperação da terapêutica e contribuindo também para o incremento dos valores da modulação global e nos valores de colesterol.…”
Section: Discussionunclassified
“…We expect to increase our study sample in the following months and thus provide further results. The main strength of this study is that it was conducted in one of the six reference centres for the treatment of COVID-19 in women in Lombardy, the first region to be affected by the disease in Europe and one of the areas with the highest diffusion rate of infection [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Among women with high‐risk pregnancies, those with gestational diabetes (GD) represent one of the largest subgroups. 4 , 5 The prevalence of GD is estimated at around 18% of pregnancies. 4 …”
Section: Introductionmentioning
confidence: 99%
“…To date, although many risk factors for GDM have been identified (e.g., maternal age, obesity, and lipid Clinicians usually use BMI, VAT, and subcutaneous adipose tissue (SAT), to assess obesity when trying to predict GDM. However, SAT is not a good predictor for GDM during the first trimester [17,18]; neither is BMI [4,5,19]. Over recent years, several studies have revealed that VAT could be a good predictor for GDM in the first and second trimesters [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, SAT is not a good predictor for GDM during the first trimester [17,18]; neither is BMI [4,5,19]. Over recent years, several studies have revealed that VAT could be a good predictor for GDM in the first and second trimesters [18,19]. It remains unclear whether EAT, as a special type of VAT, exerts a similar performance when screening for GDM.…”
Section: Discussionmentioning
confidence: 99%